Phylogenetics and morphology evolution of the family Cosmetidae Koch, 1839 (Arachnida: Opiliones): the curious case of Cosmetidae - Damron, Brittany Nicole (2020)
The family Cosmetidae (Arachnida: Opiliones) is the most diverse harvestmen family in Central America, second to the family Gonyleptidae in the Neotropics. They remain a poorly studied group, and benefit from any systematic work. This PhD research is an attempt at understanding the relationships within the family Cosmetidae. Multiple optimality criteria were used, total evidence using direct optimization in POY and Maximum Likelihood in RAxML, and molecular only using Bayesian in BEAST, divergence dating were also calculated in BEAST. Five molecular markers were used (28S rRNA, 12S rRNA, 16S rRNA, COI, and H3), and 95 morphological characters (i.e. genitalia characters, dorsal scutum outline, dorsal scutum armature) to determine clades. Analyses demonstrate that the current subfamilies of Cosmetidae (Discosomaticinae and Cosmetinae) are not valid, and the subfamily Cosmetinae is a paraphyletic group. While some monophyly of genera is implied in this analysis (see Taito, Metalibitia, and Ferkeria), other genera rediagnosed in recent literature are not (Cynorta, Paecileama, and Flirtea). It was demonstrated in these analyses that geographic range and therefore shared history is an important characteristic to consider when defining clades. A new subfamily is proposed here, supported by phylogenetic hypotheses and morphology. Preliminary divergence dating analyses shows that the family Cosmetidae is more than 10 million years older than originally estimated, with an age of approximately 47±5 myr. New diagnoses of species, genera, and subfamilies within the family Cosmetidae should focus on genitalia characters, and biogeographic region of species in the groups